2012 Sixth International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing 2012
DOI: 10.1109/imis.2012.96
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of Wrist-Worn Accelerometer Based Detection of Smoking Habits

Abstract: Cigarette smoking is one of the major causes of lung cancer, and has been linked to a large amount of other cancer types and diseases. Smoking cessation, the only mean to avoid these serious risks, is hindered by the ease to ignore these risks in day-to-day life. In this paper we present a feasibility study with smokers wearing an accelerometer device on their wrist over the course of a week to detect their smoking habits based on detecting typical gestures carried out while smoking a cigarette. We provide a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 7 publications
0
40
0
Order By: Relevance
“…Scholl and van Laerhoven [9] presented a feasibility study with smokers wearing an accelerometer device on their wrist over the course of a week to detect their smoking habits based on detecting typical gestures carried out while smoking a cigarette. The Gaussian method was used as a classifier.…”
Section: Related Workmentioning
confidence: 99%
“…Scholl and van Laerhoven [9] presented a feasibility study with smokers wearing an accelerometer device on their wrist over the course of a week to detect their smoking habits based on detecting typical gestures carried out while smoking a cigarette. The Gaussian method was used as a classifier.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, they investigate the smartwatch's camera to take images of the food being consumed to analyze what a user is eating. A feasibility study on smoking detection using a wrist-worn accelerometer is done in [134], where the authors reported a user-specific accuracy of 70% for this activity. This study used only an accelerometer at the wrist position.…”
Section: Related Work 75mentioning
confidence: 99%
“…For example, a user should not be interrupted for a feedback message while typing, writing or giving a talk, but can be interrupted while having a cup of coffee or smoking. Earlier studies [126,132,133,128,130,134] have shown that such activities can be recognized using on-body motion sensors, which we discuss further in the Related Work Section 4.2. However, these studies have used the wrist and pocket positions in isolation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations